Laparascopic Management of Peptic Ulcer Perforation: Initial Experience in Chittagong Medical College Hospital - Bhuiyan, Md Nur Hossain; Chowdhury, Md Yunus Haroon; Muhsin, Syed Md; Ali, SM Ashraf; Yusuf, Omar Faruque (Journal of Chittagong Medical College Teachers’ Association, 2011)
Key Words: laparoscopic repair; early return to work; peptic ulcer performation DOI: 10.3329/jcmcta.v21i2.7731 Journal of Chittagong Medical College Teachers' Association 2010: 21(2):16-20